Seismicity of Nepal and the Surrounding Region - Thapa, Dilli Ram (Bulletin of the Department of Geology, 2018)
This study updates an earthquakes catalogue (in terms of surface-wave magnitude, Ms≥4.0) for Nepal and the surrounding region (26°-31.7° N, 79°-90° E) covering the period from 1255 to 2015 and analyze the spatio-temporal distribution patterns of seismicity. The spatial distribution of all catalogued earthquakes indicates that earthquakes are unevenly distributed in Nepal and the surrounding region with distinctly higher earthquake activity in the far western and eastern parts of Nepal than the southern part of the country. The temporal distribution of updated seismicity data (1255-2015) indicates that there are very little accounts of significant earthquakes prior to 1800. Furthermore, the temporal trend of the updated seismic catalogue clearly demonstrate the gradual increase in earthquake data during the time window 1801-1963 and considerable increase in number and quality of seismic events predominantly from 1964 onwards. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 83-86